Profundidade de mercado na BM&FBovespa: um modelo de alta frequência para estimação da profundidade de mercado da BM&FBovespa - Barros, Carlos Felipe (2013)
The objective of this paper is to estimate a dynamic market depth measure, called VNET, for Brazilian stocks using transactions data. VNET gauges the difference between the numbers of buyer- and seller-initiated trades within the time it takes for the stock price to change by at least a certain amount. It is a realized measure of liquidity for a given price deterioration, which one may track throughout the trading day to capture liquidity’s short-term dynamics. More specifically, we model the price duration using an autoregressive conditional duration (ACD) model. The predetermined nature of the ACD process is convenient because it makes it possible to forecast future changes in the liquidity of a stock. By identifying the best moment to buy or sell, the VNET is an excellent starting point for any optimal execution strategy. Our empirical findings indicate that the VNET measure of market depth depends on the bid-ask spread, volume traded, number of trades, and both expected and unexpected price durations. Finally, we also estimate the price impact of a trade by varying the increment in the definition of price duration.